2011
DOI: 10.1111/j.1365-294x.2011.05309.x
|View full text |Cite
|
Sign up to set email alerts
|

Did vicariance and adaptation drive cryptic speciation and evolution of brooding in Ophioderma longicauda (Echinodermata: Ophiuroidea), a common Atlanto-Mediterranean ophiuroid?

Abstract: Over the last decade, cryptic speciation has been discovered in an increasing number of taxa. Species complexes are useful models for the understanding of speciation processes. Motivated by the discovery of brooding specimens in the common Atlanto-Mediterranean broadcast spawning brittle star, Ophioderma longicauda, a recent study revealed the occurrence of divergent mitochondrial lineages. We analysed 218 specimens from 23 locations spread over the geographic range of the species with partial Cytochrome c Oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
95
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 84 publications
1
95
1
1
Order By: Relevance
“…Despite the closely evolutionary relationships among them, they displayed different geographic and bathymetric distributions, and contrasted phylogeographic patterns for the mitochondrial gene 16S , a fact that should be contrasted in the future with the analysis of nuclear markers to infer if they are congruent with mitochondrial data. Our study represents an important contribution in the context of phylogeography of ophiuroids, since this has only been addressed for a few taxa worldwide152324252627282930.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the closely evolutionary relationships among them, they displayed different geographic and bathymetric distributions, and contrasted phylogeographic patterns for the mitochondrial gene 16S , a fact that should be contrasted in the future with the analysis of nuclear markers to infer if they are congruent with mitochondrial data. Our study represents an important contribution in the context of phylogeography of ophiuroids, since this has only been addressed for a few taxa worldwide152324252627282930.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its use in ecological studies, this possibility has never been considered in P. corethrurus, and it could have important implications for ecology, conservation and ecotoxicology approaches (King et al, 2008). Speciation is not always necessarily paired with morphological differentiation (Hebert et al, 2004;Ahrens et al, 2007), and cryptic species are typically found in taxa that occur in complex and patchy terrestrial and aquatic habitats (Hebert et al, 2004;Hilário et al, 2010;Boissin et al, 2011;Avrani et al, 2012). In fact, the more studies are performed on annelids the more clear it becomes that cryptic speciation is not an uncommon phenomenon in this phylum (Pfenninger and Schwenk, 2007;Hilário et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They are prone to dispersal and may undergo high envi-106 ronmental variations during early development stages, but they 107 are also closely linked to a specific environment once settled on 108 or in the bottom (as juveniles and adults). They are also expected 109 to display large effective population sizes (Boissin et al, 2011;110 Foltz et al, 2003110 Foltz et al, , 2004 (Mortensen, 1951;Higgins, 1974;David and 133 Laurin, 1996;Féral et al, 1998). 134 Echinocardium cordatum occupies temperate sandy to muddy 135 habitats, ranging from the intertidal to more than 250 m deep, 136 but it is absent from American coasts (both Atlantic and Pacific) 137 (Mortensen, 1951;Buchanan, 1963Buchanan, , 1966Higgins, 1974;Féral 138 et al, 1998;Kashenko, 2007).…”
mentioning
confidence: 93%